Experimental psychology - "Dunham, Philip J." (New York, 1977)
This book covers the following topics overview of the scientific method; case history in scientific methodology; Logic of experimental design; Theory and the process approach; Learning the behavioral approach with animals; Learning the behavioral approach with Human; Learning the physiological approach; Motivational the behavioral approach with animals; Motivational the behavioral approach with Human; Motivational the physiological approach; Perception the behavioral approach; Perception the physiological approach.
Keywords: "Psychology, Experimental"